Assessment of Selected Morphological Traits of Sweet Chestnut (Castanea sativa Mill.) Fruits from Repository Príbelce (Slovakia) - Horčinová Sedláčková, Vladimíra; Mňahončáková, Erika; Grygorieva, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Sweet chestnut (Castanea sativa Mill.) as an introduced species in Slovakia is the object of our research in terms of morphometric analysis of fruits from randomly selected 30 genotypes from the repository Príbelce with presence of old varieties, biennial seedlings of intraspecific and interspecific hybrids and individuals from free pollination from the Arboretum Mlyňany and M.M. Gryshka National Botanical Garden of National Academy of Sciences of Ukraine in Kyiv. In the characteristics and evaluation of fruit characters, we determined high variability in all quantitative and qualitative traits. The collection recorded significant differences in fruit weight in the range of 2.08–13.21 g with a coefficient of variation in the interval 7.12–34.26%, average fruit height 15.50–30.37 mm (3.62–14.79%), fruit width 17.80–34.51 mm (3.62–15.10%), hilum length 13.31–29.20 mm (6.22–16.75%), hilum width 7.12–15.87 mm (6.49–17.50%) and a nut hairiness of 9.81–22.39 mm (6.75–20.65%). According to the fruit shape index, we determined a triangular, spherical, transversely elliptical and transversely broad-elliptical shape in the collection of genotypes. The results of the research point to the fact that the Castanea sativa genetic material from the clone repository is a rich source of genetic diversity and can be used in the selection to create new varieties and cultivars.